Ubóstwo i bogactwo w Polsce na początku XXI wieku. Ocena neoliberalizmu z punktu widzenia katolickiej nauki społecznej - Wójcik, Stanisław (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The theory and practice of modern capitalism results in the moral and intellectual degradation of man, limits his rights, and drives him to poverty, while affluence is accessible only to the few. The fundamental error of the system concerns the omnipotence of the market and free competition. An increasing part of society is driven to passivity. Catholic social teaching promotes a social market economy where both the social state and the people care for the common good.
Poverty and affluence in Poland in the early 21 st century. The assessment of neoliberalism from the perspective of Catholic social teaching